The African Christian diaspora: new currents and emerging trends in world Christianity - Adogame, Afe (Bloomsbury Academic, 2013)
The last three decades have witnessed a rapid proliferation of African Christian communities, particularly in Europe and North American diaspora, thus resulting in the remapping of old religious landscapes. This migratory trend and development bring to the fore the crucial role, functions and import of religious symbolic systems in new geo-cultural contexts. The trans-national linkages between African-led churches in the countries of origin (Africa) and the ""host"" societies are assuming increasing importance for African immigrants. The links and networks that are established and maintained b